Socio-economic Impacts of Tourism in Lumbini, Nepal: A Case Study - Acharya, Pradeep (Dhaulagiri Journal of Sociology and Anthropology, 2006)
DOI: 10.3126/dsaj.v1i0.290 Dhaulagiri Vol.1 (2005) pp.193-206